The Effect of Interactive Learning Media on Students’ Ability to Create Comic Storyboards from Drama Texts - Dinda Pratiwi; Asri Yulianda; Nurhanna Harahap (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the impact of interactive learning media on students’ ability to create comic storyboards from drama texts, addressing the issue of low student interest due to traditional teaching methods. The study aims to: (1) assess students’ learning outcomes before using interactive learning media, (2) evaluate their learning outcomes after its implementation, and (3) determine whether interactive learning media significantly influences students’ ability to create comic storyboards. This research employs a quantitative approach using an experimental and control group design. Data collection was conducted through pretest and posttest assessments. The findings indicate that before using interactive learning media, students demonstrated low comprehension of drama texts and difficulty in visualizing story structures. After implementing the media, students showed significant improvements in understanding dramatic elements, sequencing events, and creatively transforming texts into storyboards. The T-test results revealed a 34.31-point increase in learning outcomes, confirming a statistically significant effect. Furthermore, students displayed higher engagement, creativity, and participation in learning activities. These results suggest that interactive learning media is an effective tool for enhancing students’ comprehension of drama texts and their ability to translate them into visual narratives.